Counselling Patients with Uterine Fibroids: A Review of the Management and Complications - Donnette Simms-Stewart; Horace Fletcher (Hindawi Limited, 2012)
Fibroids are very common in Afro-Caribbean women. They can cause severe complications. The treatment modalities are not without risk and should be weighed against the complications of the fibroids.